Hypothesis on the outflow of optic nerve cerebrospinal fluid in spaceflight associated neuro ocular syndrome - Yuwei Hu; Yuanxi Lin; Lu Cheng; Yang Xu; Jian Zhang; Zheng Zheng; Huan Wang; Min Yan; Hui Chen (npj Microgravity)
Abstract Spaceflight-associated neuro-ocular syndrome (SANS) has been well documented in astronauts. However, its pathogenesis is not fully understood. New findings indicate the impaired outflow of the optic nerve cerebrospinal fluid may participate or contribute to some changes in SANS. In this perspective, we generated a hypothesis that the outflow of cerebrospinal fluid through the optic nerve sheath may be impaired under micro-gravity and then may potentially lead to SANS-related alterations.